2002
DOI: 10.1128/jb.184.16.4544-4554.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of thePseudomonas aeruginosaResponse Regulator AlgR Is Essential for Type IV Fimbria-Mediated Twitching Motility

Abstract: The response regulator AlgR is required for both alginate biosynthesis and type IV fimbria-mediated twitching motility in Pseudomonas aeruginosa. In this study, the roles of AlgR signal transduction and phosphorylation in twitching motility and biofilm formation were examined. The predicted phosphorylation site of AlgR (aspartate 54) and a second aspartate (aspartate 85) in the receiver domain of AlgR were mutated to asparagine, and mutant algR alleles were introduced into the chromosome of P. aeruginosa strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 45 publications
7
108
0
Order By: Relevance
“…Two independent insertions that had the same consequences for the interaction with D. melanogaster have been found in algR. In P. aeruginosa, AlgR regulates a number of processes including fimbrial biogenesis, biofilm formation and cyanide production 25,26 . Altogether, genetic analysis indicates that GacA is a master regulator of the interaction and that PrtR and AlgR regulators, seem to play secondary roles in the infection process.…”
Section: Regulation Of Virulence Revealed By a Genome-wide Mutagenesismentioning
confidence: 85%
“…Two independent insertions that had the same consequences for the interaction with D. melanogaster have been found in algR. In P. aeruginosa, AlgR regulates a number of processes including fimbrial biogenesis, biofilm formation and cyanide production 25,26 . Altogether, genetic analysis indicates that GacA is a master regulator of the interaction and that PrtR and AlgR regulators, seem to play secondary roles in the infection process.…”
Section: Regulation Of Virulence Revealed By a Genome-wide Mutagenesismentioning
confidence: 85%
“…The surface-dependent induction of algC expression correlated with stability of attachment, with cells that did not undergo algC upregulation demonstrating reduced ability to remain attached to the surface relative to that of cells with activated expression (33). While these findings suggested increased alginate production upon attachment, with alginate production contributing to biofilm resistance and being inversely linked to both flagellum-driven motility and twitching motility (48,139,165), it is now apparent that alginate is neither the major matrix polysaccharide nor required for biofilm development by nonmucoid P. aeruginosa strains, which are the first to colonize CF patients (121,144,167). Instead, recent chemical and genetic studies have demonstrated that the major polysaccharides produced by P. aeruginosa strains PAO1 and PA14 are Psl and Pel, with the roles of these two polysaccharides differing with respect to attachment and biofilm formation in a strain-specific manner.…”
Section: Figmentioning
confidence: 99%
“…Type IV pili are flexible surface filaments about 6 nm in diameter produced at the poles of the bacterial cell (Beatson et al, 2002;; they are essential for the attachment of the pathogen to host epithelial tissues and also mediate a form of surface translocation known as twitching motility (Bradley, 1980;. Twitching motility has been shown to be required for the initial attachment and development of a biofilm by P. aeruginosa (O'Toole & Kolter, 1998;Costerton et al, 1999;Mcbride, 2001;Whiteley et al, 2001;Whitchurch et al, 2002). Once a biofilm is developed, cells growing in the biofilm can become 10-1000 times more resistant to the effects of antibiotics than their planktonic counterparts (Mah & O'Toole, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm bacteria embedded in an extracellular polymeric matrix cannot be eradicated even with the most aggressive antibiotics. Mutants that either lack type IV pili or are twitchingmotility deficient show loss of ability for biofilm initiation (O'Toole & Kolter, 1998) and reduced infectivity (Kang et al, 1997;Whitchurch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%